THE IMPACT OF SCANNING AND SKIMMING TECHNIQUES ON READING COMPREHENSION AND TASK EFFICIENCY IN ENGLISH LANGUAGE LEARNERS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: Many methods are used to improve the reading skills of students learning English as a second language in preparation for certification. Scanning and skimming are considered as the most important methods to boost reading skills. These methods help students to understand the main content and essence of the given text and to find them in a short time.